The Comprehensive Assessment of Acceptance and Commitment Treatment Process (Compact): Adaptation of The Indonesian Version - Gitta Suganda; Fitri Ariyanti Abidin (Journal of Educational, Health and Community Psychology, 2022)
The Comprehensive Assessment of Acceptance And Commitment Treatment Process (CompACT) measures a person's psychological flexibility abilities. This measurement has been validated in several languages. However, this instrument has not adapted the Indonesian context yet Therefore, the current study aims to examine the validity and reliability of the Indonesian version of CompACT. The adaptation procedures followed the five steps of test adaptation suggested by the International Test Commission. According to the calculation of V'Aiken, 13 items out of 23 original items are valid through expert judgment. Four hundred and forty adult (male = 131, female = 319; M age = 35.49; SD = 13.80) participated in a questionnaire survey. CFA test showed a fit model of the Indonesian version ofÂ  CompACT (X2 (62, N = 440) = 191.94, p > .05, RMSEA = .068, CFI = 0.95, GFI = 0.94, NFI = 0.92 SRMR = 0.054, t-values = 7.97 â€“ 16.38). The factor structure supported the original three factors, namely Openness to Experience (2 items), Behavioral Awareness (4 items), and Valued Action (7 items). The internal consistency for each dimension is .445, .806, and .790 respectively. The result implied that CompACT is a valid and reliable instrument to assess Indonesian psychological flexibility abilities.